Effects of temperature on decomposition of a potential nuisance species: the submerged aquatic macrophyte Egeria najas planchom (Hydrocharitaceae) - Carvalho,P (2005)
Decomposition of aquatic plants is influenced by several biotic and abiotic factors. Among them, temperature plays an important role. Despite the increasing number of studies describing the effects of temperature on the decomposition of aquatic macrophytes, little attention has been given to the decay of submerged macrophytes. In this paper, we assessed the effect of temperature on weight loss and chemical composition of detritus of the submerged aquatic macrophyte Egeria najas Planchon (Hydrocharitaceae). Fresh plant material was maintained at 17ºC and 27ºC, in the dark, in incubation chambers. The overall decay process was best described by a linear model, with rates of 0.014 day-1 (R² = 94%) and 0.045 day-1 (R² = 96%) obtained at 17ºC and 27ºC, respectively. The analysis of covariance (ANCOVA) indicated a significant difference between the decomposition rates at the two temperatures. The rapid breakdown of E. najas detritus, indicated by the decay coefficient, may be explained by its low content of resistant compounds such as cellulose and lignin. The variables analyzed in this study (pH, electrical conductivity, dissolved oxygen in the water and organic matter, total nitrogen and total phosphorus concentration in detritus) showed accentuated responses at 27ºC. It is likely that the higher temperature increased microbial activity and, therefore, oxygen consumption in the water, consequently affecting the pH and the rate of ion and nutrient liberation into the aquatic ecosystem. Due to the rapid decomposition of E. najas at high temperatures, a small exportation is expected of this species from its stands to distant regions in tropical reservoirs, where it is considered a potential nuisance species.